Inadequate Prenatal Care Utilization and Risks of Infant Mortality and Poor Birth Outcome: A Retrospective Analysis of 28,729,765 U.S. Deliveries over 8 Years - Partridge, Sarah; Balayla, Jacques; Holcroft, Christina A.; Abenhaim, Haim A. (American Journal of Perinatology, 2012)
Objective To evaluate the association between adequacy of prenatal care utilization and risk of fetal and neonatal mortality and adverse outcomes.Methods We conducted a population-based cohort study using the Center for Disease Control and Prevention's Linked Birth-Infant Death and Fetal Death data on all deliveries in the United States between 1995 and 2002. Inclusion criteria were singleton births ≥22 weeks of gestation with no known congenital malformation. Inadequate prenatal care was defined according to the Adequacy of Prenatal Care Utilization Index, and its effect on fetal and neonatal death was estimated using unconditional logistic regression analysis adjusting for maternal age, race, education, and other confounding variables.Results During our 8-year study period, 32,206,417 births occurred, 28,729,765 (89.2%) of which met inclusion criteria. Inadequate prenatal care utilization occurred in 11.2% of expectant mothers, more commonly among women ≤20 years, black non-Hispanic and Hispanic women, and those without high school education. Relative to adequate care, inadequate care was associated with increased risk of prematurity 3.75 (3.73 to 3.77), stillbirth 1.94 (1.89 to 1.99), early neonatal dearth 2.03 (1.97 to 2.09), late neonatal death 1.67 (1.59 to 1.76), and infant death 1.79 (1.76 to 1.82).Conclusion Risk of prematurity, stillbirth, early and late neonatal death, and infant death increased linearly with decreasing care. Given the population effect of this association, public health initiatives should target program expansion to ensure timely and adequate access, particularly for women ≤20 years, Black non-Hispanic and Hispanic women, and those without high school education.
Keywords: prenatal care; risk factors; pregnancy outcome; infant mortality; population characteristics